Underlying factors in Finish students’ good results (Journal of Parents and Teachers, 2012)
Finish students’ good results set them apart from the rest of students in Europe and this is due to several factors such as the school, the culture, the social-economic factor and the teachers’ training. In reference to this last point, the main approaches for teacher training in Finland are about investigating attitude, professionalism, commitments, cooperation and interaction, autonomy, active learning, cooperative methods.
Keywords: results; factors; teacher training